The anticancer activities of stichoposide D isolated from the sea cucumber Stichopus chloronotus on NTERA-2 cancer stem cells - Cuc, Nguyen Thi; Thi Nga, Nguyen; Ha Phuong, Trieu; Thi Phuong, Do; Xuan Cuong, Nguyen; Thi Mai Huong, Pham; Van Minh, Chau; Thi Thao, Do (Vietnam Journal of Biotechnology, 2020)
As reported, cancer stem cells (CSCs) are in charge of dangerous characteristics including drug resistance, metastasis, recurrence and therapeutic effectiveness. Therefore, CSCs are an important target for discovering of novel effective and specific anticancer drugs. In Vietnam, the Stichopus chloronotus sea cucumber is found as a potential biological source with various active ingredients. Particularly, the active triterpene saponin stichoposide D, which was isolated from S. chloronotus, showed strong cytotoxic activity in leukemias. Herein, stichoposide D was further studied its potential anti-CSCs activities on pluripotent human embryonic carcinomas NTERA-2 cells. The compound exhibited its promising and specific cytotoxic activities in NTERA-2 cells with the IC50 = 0.26 ± 0.02 µM, in comparison with that ranging from 0.35 ± 0.02 µM to 0.53 ± 0.03 µM (P<0.05), tested on non-CSCs cancer cell lines, which were breast carcinoma (MCF-7) and lung adenocarcinoma (SK-LU-1), respectively. The working fashion of the compound on NTERA-2 cells could be apoptotic induction. Significantly, treatment of stichoposide D at 1 µM induced 76.4% of apoptotic cells as well as 1.72 relatively fold change of caspase-3 activation in comparision with the control (P<0.05). Meanwhile, stichoposide D was the first time recorgnized its positive efficacy on reducing the number of highly expressed CD44+/CD24+ cells, which were reported as typically CSCs characterized population. The compound also exhibited some effects on NTERA-2 cell cycle of which it arrested cells at sub-G1 phase (15.03%) and prevented those CSCs to enter the S-phase for DNA synthesis. In conclusion, stichoposide D presents potential anti-CSCs activities and should be further studied for future applications.